The Treponema denticola AtcR LytTR domain‐containing response regulator interacts with three architecturally distinct promoter elements: implications for understanding the molecular signaling mechanisms that drive the progression of periodontal disease. (24th July 2014) - Miller, D.P.; Frederick, J.R.; Sarkar, J.; Marconi, R.T.
Summary Treponema denticola is an oral spirochete and periopathogen that transitions from low abundance in healthy subgingival crevices to high abundance in periodontal pockets. The T. denticola response regulator AtcR harbors the relatively rare, LytTR DNA‐binding domain. LytTR domain containing response regulators control critical transcriptional responses required for environmental adaptation. Using a multi‐step bioinformatics approach, 26 strong lytTR recognition motifs were identified in the genome of T. denticola strain 35405. Electrophoretic mobility shift assays demonstrated that AtcR binds to these recognition motifs. High specificity–high affinity complexes formed with phosphorylated AtcR. The LytTR recognition sequences were found to exist in three distinct promoter architectures designated as LytTR1, LytTR2 and LytTR3 promoters. LytTR1 and LytTR2 promoters harbor σ54 binding sites. The functional diversity of the proteins encoded by the putative AtcR regulon suggests that AtcR sits at the top of a regulatory cascade that plays a central role in facilitating T. denticola's ability to adapt to changing environmental conditions and thrive in periodontal pockets.